Cross-Sectional Associations Between Measures of Sleep and Markers of Glucose Metabolism Among Subjects With and Without Diabetes: The Coronary Artery Risk Development in Young Adults (CARDIA) Sleep Study - KNUTSON, Kristen L; VAN CAUTER, Eve; ZEE, Phyllis; LIU, Kiang; LAUDERDALE, Diane S (Diabetes care, 2011)
To examine whether sleep duration and quality are associated with fasting glucose, fasting insulin, or estimated insulin resistance in a community-based sample of early middle-aged adults. This was an ancillary study to the Coronary Artery Risk Development in Young Adults (CARDIA) Study. Habitual sleep duration and fragmentation were estimated from 6 days of wrist actigraphy collected in 2003-2005. Insomnia was defined as self-reported difficulty falling asleep or waking up in the night three or more times per week plus average sleep efficiency of <80% based on actigraphy. Fasting blood samples to measure glucose and insulin were collected after the sleep measures during the CARDIA clinical examination in 2005-2006. Insulin resistance was estimated using the homeostatic model assessment (HOMA) method. Analyses were cross-sectional and stratified by the presence of diabetes. There was no association between sleep measures and fasting glucose, insulin, or HOMA in the 115 subjects without diabetes. Among the 40 subjects with diabetes, after adjustment for covariates, 10% higher sleep fragmentation was associated with a 9% higher fasting glucose level, a 30% higher fasting insulin level, and a 43% higher HOMA level. Insomnia was associated with a 23% higher fasting glucose level, a 48% higher fasting insulin level, and an 82% higher HOMA level. The observed association between poor sleep quality and higher glucose, insulin, and estimated insulin resistance among subjects with diabetes warrants further examination of the effect of sleep disturbances on glucose control in type 2 diabetes.